Fiscal space of Brazilian states - Bastos, Fabiano (2013)
We estimate the fiscal space of Brazilian states defined as the difference between a state's actual debt and the theoretical debt limit implied by the historical behavior of its policymakers. Fiscal reaction functions and debt limits are estimated using publically available data between 2000 and 2011 for the 26 Brazilian states and the Federal District. The results suggest that after a decae of fiscal consideration, a number of states have fiscal space but there remains significant heterogeneity across states. Going forward, enhancing the role of market incentives and strengthening rules-based approaches governing sub-national debt build-up would contribute to a prudent and effective use of existing fiscal space.